Evaluation of coumarins effect in saccharomyces cerevisiae - Pinto, D. (2013)
Coumarin and derivates (coumarins) are phenolic compounds widely distributed in the plant kingdom, as for example in tonka beam and cassia cinnamon. These compounds are involved in various processes such as the defense against phytopathogens, the response to abiotic stress and the regulation of oxidative stress. Coumarins can be produced synthetically and are broadly used as additives in the food, perfumes and cosmetics and pharmaceutical industry due th their vast array of biological activities, including anticoagulant, analgesic, anti-inflammatory and anti-microbial.